Questão de Gênero na Literatura Latino-Americana - Hurtig, Janise D.; Solar, Rosário Montoya de (Locus: Revista de História, 2000)
Resenha do texto "House, Garden, Nation: Space, Gender and Ethnicity in Post-Colonial Latin American Literatures by Women" (1994), da autora Ileana Rodriguez.